Temperature Effects on Cuscuta campestris Yunk. Seed Germination - Sarić-Krsmanović, Marija M; Božić, Dragana; Pavlović, Danijela; Radivojević, Ljiljana; Vrbničanin, Sava (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
Studies of biological characteristics of seeds and conditions for their germination have a major importance for planning and executing rational measures of weed control. The aim of this study was to investigate the effect of different temperatures on germination of C. Campestris seeds. Three treatments (T1- storage at room temperature; T2 – exposure to 4°C for 30 days; T3 – scarification by concentrated sulphuric acid) differing in manipulation with seeds before germination were tested at different temperatures (5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C). Germinated seeds were counted daily for ten days and the length of seedlings was measured on the last day. The results showed that differences in germination of C. campestris seeds were very prominent between temperatures, as well as between treatments T1, T2 and T3. Seeds failed to germinate at 5°C and 45°C in all treatments (T1, T2, T3). Germination ranged from 6.25 at 10°C to 96.88%, the highest percentage, achieved at 30°C.